Mother-Tongue Based Multilingual Education (MTBMLE) Initiatives in Region 8 - Voltaire Q. Oyzon; John Mark Fullmer (Institute of Advanced Engineering and Science, 2014)
With the implementation of Mother-Tongue Based Multilingual Education (MTBMLE) under the Enhanced Basic Education Act of 2013, this study set out to examine Region 8’s readiness and extant educational materials. On the one hand, “L1 to L2 Bridge Instruction” has been shown by Hovens (2002) to engender the most substantive language acquisition, while the “Pure L2 immersion” approach displays the lowest results. Despite this, Region 8 (like other non-Tagalog speaking Regions) lacks primary texts in the mother tongue, vocabulary lists, grammar lessons and, more fundamentally, the references needed for educators to create these materials. To fill this void, the researchers created a 377,930-word language corpus generated from 419 distinct Waray texts, which led to frequency word lists, a five-language classified dictionary, a 1,000-word reference dictionary with pioneering part-of-speech tagging, and software for determining the grade level of Waray texts. These outputs are intended to be “best practices” models for other Regions. Accordingly, the researchers also created open-source, customizable software for compiling and grade-leveling texts, analyzing the grammatical nuances of each local language, and producing vocabulary lists and other materials for the Grade 1-3 classroom.DOI: http://dx.doi.org/10.11591/ijere.v3i1.5862